Efforts of Raising Intelligence in Order to Prevent the Implementation of Community Security Due to Dispute Development of Cipali Toll Road by Majalengka Security Intelligence Police Resort - Pardede, Charles Rio Valentine (Indonesian Journal of Police Studies, 2024)
The construction of toll roads in the territory of Indonesia. Specifically in the construction of the Cipali toll road, which caused various impacts on community security. This is motivated by the intersection of the Republic of Indonesia's State Goals and the fact of Komnas HAM that the issue of toll disputes has become a national problem, causing the impact of community security including demonstrations, destruction of toll facilities, and blockading of the Cipali toll road that occurred from 2015 until now. This requires the police to play an active role in carrying out their duties. The issues raised in this study were analyzed using proactive police iceberg theory, intelligence management theory, strategic management theory, the concept of effort, the concept of intelligence, and the concept of raising intelligence. The author uses a qualitative approach. Data collection uses interview, observation and document review methods. Data analysis by data reduction, data presentation and conclusion drawing. Through the police function, especially the security intelligence (Intelkam) function, the National Police has made a preemptive effort to raise intelligence aimed at monitoring the movement of pros and cons in the Cipali dispute. This thesis discusses a general picture of the impact of Kamtibmas that occurs, the implementation of intelligence unit's duties in carrying out intelligence raising and the intelligence unit's efforts in carrying out intelligence raising. The results of the study showed that Majalengka Police Intelligence Unit's efforts in carrying out the target were indicated to endanger the condition of Community Security, by mapping the implementation of which was still not optimal. The implementation of the task has not been carried out according to the procedures set out in Perkabik No 3 of 2013. Several factors also influenced intelligence-raising efforts in preventing the impact of Community Security in Majalengka District. Intelligence raising activities have been carried out by the Intelligence Unit with the aim that they can be resolved immediately and can create the expected Community security conditions.